Clathrate Hydrates of Organic Solvents as Auxiliary Intermediates in Pharmaceutical Research and Development: Improving Dissolution Behaviour of a New Anti-Tuberculosis Drug, Perchlozon - Andrey G. Ogienko; Svetlana A. Myz; Andrey A. Nefedov; Anna A. Ogienko; Tatyana P. Adamova; Olga M. Voronkova; Svetlana V. Amosova; Boris A. Trofimov; Vladimir V. Boldyrev; Elena V. Boldyreva (MDPI AG, 2022)
There is an urgent need for new drugs to overcome the challenge of the ever-growing drug resistance towards tuberculosis. A new, highly efficient anti-tuberculosis drug, Perchlozone (thioureidoiminomethylpyridinium perchlorate, Pz), is only available in an oral dosage form, though injectable forms and inhalation solutions could be better alternatives, offering higher bioavailability. To produce such forms, nano- and micro-particles of APIs would need to be prepared as dispersions with carriers. We use this case study to illustrate the principles of selecting solvents and excipients when preparing such formulations. We justify the choice of water-THF (19.1 wt % THF) as solvent and mannitol as carrier to prepare formulations of Pz-a poorly soluble compound-that are suitable for injection or inhalation. The formulations could be prepared by conventional freeze-drying in vials, making the proposed method suitable for industrial scaling. A similar strategy for selecting the organic solvent and the excipient can be applied to other compounds with low water solubility.